2010
DOI: 10.1148/radiol.10092396
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cell Carcinoma: Diffusion-weighted MR Imaging for Subtype Differentiation at 3.0 T

Abstract: DW imaging with b values of 0 and 800 sec/mm(2) allows sensitive and specific differentiation of clear cell, papillary, and chromophobic RCCs, suggesting that DW imaging may be useful in the preoperative characterization of RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
140
0
4

Year Published

2012
2012
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(150 citation statements)
references
References 36 publications
(34 reference statements)
6
140
0
4
Order By: Relevance
“…A potential alternative to increased use of biopsy might lie in the use of diagnostic imaging to characterize renal cortical tumors on the basis of their tissue composition, morphologic features, and/or contrast enhancement patterns (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Doppler ultrasonography, contrast material-enhanced computed tomography, and magnetic resonance (MR) imaging have shown potential for enabling differentiation of clear cell renal carcinomas (which show increased vascular flow and enhance avidly) from papillary and chromophobe carcinomas (which show reduced vascular flow and less enhancement) (21)(22)(23)(24)(26)(27)(28)).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A potential alternative to increased use of biopsy might lie in the use of diagnostic imaging to characterize renal cortical tumors on the basis of their tissue composition, morphologic features, and/or contrast enhancement patterns (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Doppler ultrasonography, contrast material-enhanced computed tomography, and magnetic resonance (MR) imaging have shown potential for enabling differentiation of clear cell renal carcinomas (which show increased vascular flow and enhance avidly) from papillary and chromophobe carcinomas (which show reduced vascular flow and less enhancement) (21)(22)(23)(24)(26)(27)(28)).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Wang et al (31) showed that clear cell carcinomas had significantly higher apparent diffusion coefficients than did papillary or chromophobe carcinomas. Taouli et al (30) reported that in the differentiation of benign and malignant renal lesions, DW MR imaging (area under the receiver operating characteristic curve, 0.85) was less accurate than qualitative assessment of dynamic contrastenhanced MR imaging (area under the receiver operating characteristic curve, 0.94).…”
Section: Genitourinary Imaging: Renal Cortical Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…DWI provides quantification of the Brownian motion of water molecules in tissues, which depends on tissue organization, cellularity, the integrity of cell membranes, and extracellular space tortousity (21). Qualitative and quantitative information are obtained regarding tissue characterization without the need for gadolinium chelates and alternative imaging for renal lesion characterization in patients at risk for nephrogenic systemic fibrosis (21)(22)(23)(24). Few studies have evaluated the correlation of apparent diffusion coefficient (ADC) values with nuclear grade, histological subtype, and cellularity of RCC.…”
Section: The Role Of Mri In Renal Imagingmentioning
confidence: 99%
“…To date, only 2 studies, which examined only RCC but not benign renal tumors, have used MRI at 3T. 21,22 The purpose of this study was to assess the usefulness of the apparent diffusion coefficients (ADCs) for differentiating different types of solid renal tumors with DWI at 3T.…”
Section: Introductionmentioning
confidence: 99%